Allergic sensitization, rhinitis, and tobacco smoke exposure in U.S. children and adolescents. Issue 6 (17th April 2015) - Shargorodsky, Josef; Garcia‐Esquinas, Esther; Navas‐Acien, Ana; Lin, Sandra Y.
<x xml:space="preserve">Abstract</x> Background Childhood tobacco exposure has been linked with sinonasal pathology, and may be associated with allergic sensitization. This study evaluates the association between exposure to active smoking or secondhand smoke (SHS) and the prevalence of rhinitis and allergic sensitization in the U.S. pediatric population. Methods Cross‐sectional study in 2714 children and adolescents aged 6 to 19 in the National Health and Nutrition Examination Survey (NHANES), 2005–2006. Active smoking was defined as self‐reported smoking or serum cotinine concentrations >10 ng/mL. SHS was defined as nonactive smokers who reported living with ≥1 smokers or had serum cotinine ≥0.011 ng/mL. Self‐reported rhinitis was based on symptoms during the past 12 months, and allergen sensitization was defined as a positive response to any of the 19 specific immunoglobulin E (IgE) antigens tested. Results About half of the population (54%) had detectable levels of IgE specific to at least 1 of the tested allergens, and 25% reported a history of rhinitis. After multivariate adjustment, an increased prevalence rate ratio (PRR) of self‐reported rhinitis was seen in individuals in the highest cotinine tertile among active smokers (PRR, 1.73; 95% confidence interval [CI], 1.23 to 2.43), with a significant trend between increasing cotinine levels in individuals exposed to either secondhand smoke or active smoking (p = 0.05 for both analyses). Significantly less food allergen sensitization was observed in participants in the highest cotinine tertile of secondhand smoke (PRR, 0.61; 95% CI, 0.43 to 0.85). Conclusion Tobacco smoke exposure was associated with increased prevalence of rhinitis symptoms, but decreased prevalence of allergic sensitization. The results highlight the complex relationship between tobacco exposure and sinonasal pathology.